1980
DOI: 10.1177/106002808001400710
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of Adverse Effects during Chronic Therapy with Theophylline

Abstract: Recent definition of the pharmacodynamics and pharmacokinetic characteristics of theophylline and readily available, specific assays have increased the therapeutic benefits of this drug while decreasing the risk of toxicity. Once familiarity is achieved with the various factors that can alter clearance, such as age, smoking habits, physiological abnormalities, and concurrent drug therapy, an initial dosage can be appropriately individualized. Careful product selection, the slow progressive titration of dose ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In the steadystate study with 800 mg, 14.8% of the pa tients presented gastrointestinal com plaints, which is comparable to the data with other theophylline preparations. At that moment, the plasma theophylline concentrations were within therapeutic ranges, which is not unexpected since such adverse effects may, indeed, occur with therapeutic or even subtherapeutic levels, and are often not strictly related to plasma theophylline concentrations [7], Yet, 1 pa tient on 1,200 mg daily had to interrupt the treatment because of serious gastrointesti nal complaints and tachy-dysrhythmia due to a supratherapeutic plasma concen tration of 20.5 ¿¿g/ml. In this patient the plasma concentrations were 13.1 /xg/ml on 800 mg and 8.1 jug/ml on 400 mg.…”
Section: Discussionmentioning
confidence: 83%
“…In the steadystate study with 800 mg, 14.8% of the pa tients presented gastrointestinal com plaints, which is comparable to the data with other theophylline preparations. At that moment, the plasma theophylline concentrations were within therapeutic ranges, which is not unexpected since such adverse effects may, indeed, occur with therapeutic or even subtherapeutic levels, and are often not strictly related to plasma theophylline concentrations [7], Yet, 1 pa tient on 1,200 mg daily had to interrupt the treatment because of serious gastrointesti nal complaints and tachy-dysrhythmia due to a supratherapeutic plasma concen tration of 20.5 ¿¿g/ml. In this patient the plasma concentrations were 13.1 /xg/ml on 800 mg and 8.1 jug/ml on 400 mg.…”
Section: Discussionmentioning
confidence: 83%
“…This, however, may be unrealistic for narrow therapeutic range drugs, such as theophylline, whose minimum effective concentration and minimum toxic concentration are generally accepted to be 10 and 20 mg/L, respectively. [17][18][19] For these drugs, it might be most practical to operate in the medium-risk area (delineated sea green in Fig. 6) so as to mitigate the likelihood of either adverse outcome.…”
Section: Design Spacementioning
confidence: 99%
“…Theophylline is one of the most effective bronchodilators used for chronic obstructive pulmonary diseases (Hendeles & Weinberger, 1980). Factors which impair the elimination of theophylline can cause accumulation of the drug and result in serious side effects in patients who receive multiple dose therapy (Hendeles & Weinberger, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Factors which impair the elimination of theophylline can cause accumulation of the drug and result in serious side effects in patients who receive multiple dose therapy (Hendeles & Weinberger, 1980). Recent reports have suggested that viral infections decrease theophylline elimination rates and cause serious toxicity in some patients (Chang et al, 1978;Clarke & Boyd, 1979;Fleetham etal., 1978;Vozeh et al, 1978).…”
Section: Introductionmentioning
confidence: 99%